2004
DOI: 10.3751/58.3.12
|View full text |Cite
|
Sign up to set email alerts
|

Princes and Parliaments in the Arab World

Abstract: Several Arab monarchies have held reasonably free elections to parliaments, though all remain authoritarian. This article compares the Arab monarchies with parliaments in other parts of the world, including both those that became democracies, and those that did not. From this I derive a set of prerequisites, potential pitfalls, and expected stages in the monarchical path toward democracy. This helps us to understand not only the democratic potential of the parliamentary experiments in the Arab monarchies, but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…Although most agree that HBV is "by no means exclusively Muslim" (Payton, 2014(Payton, , p. 2866, scholars have documented how perpetrators and their families may use religion to justify honorrelated violence (Al Gharaibeh, 2016;Kulczycki & Windle, 2011). Others have elucidated the key role of Islamist political movements in resisting legal punishment of HBV (Herb, 2004). And, on the side of religious leaders, Idriss' (2020) study of Muslims in the United Kingdom concluded that some mosques shrink from addressing violence against women, including HBV, because it may threaten their patriarchic control over worshippers (p. 26).…”
Section: Hbv In the Middle Eastmentioning
confidence: 99%
“…Although most agree that HBV is "by no means exclusively Muslim" (Payton, 2014(Payton, , p. 2866, scholars have documented how perpetrators and their families may use religion to justify honorrelated violence (Al Gharaibeh, 2016;Kulczycki & Windle, 2011). Others have elucidated the key role of Islamist political movements in resisting legal punishment of HBV (Herb, 2004). And, on the side of religious leaders, Idriss' (2020) study of Muslims in the United Kingdom concluded that some mosques shrink from addressing violence against women, including HBV, because it may threaten their patriarchic control over worshippers (p. 26).…”
Section: Hbv In the Middle Eastmentioning
confidence: 99%
“…The two countries, Morocco and Thailand before the abortive democratization, while being vastly different on the majority of meaningful parameters, are nevertheless similar in that parliamentary elections have limited impact on the composition of the national executive, and even the legislative capacities of the elected parliaments are reduced. In Morocco, power remains largely concentrated in the hands of the king (Herb, 2004). In Thailand, the influence of the king's court used to be reinforced by its connections with powerful factions of the military (McCargo 2004).…”
Section: The Operationalization Of Key Conceptsmentioning
confidence: 99%
“…Some of them have maintained the absolutist-like asset. Yet, many others have introduced minimally competitive elections and/or limited forms of power-sharing at the legislative level, although the power of the king remains unchallenged (Herb, 2004).…”
Section: A Comparative Perspective: State Of the Art Evidence And Newmentioning
confidence: 99%